Justification of Death Penalty in Rarest of Rare Cases and Opinion for its Abolition: The Controversy Surrounding the Death Penalty in Rare Cases (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Death Sentence is the law[1] and the “Rarest of Rare Cases” is the policy. The Supreme Court’s first version in awarding the death sentence is to study whether the offence amounts to the rarest of rare cases. Its first Cardinal Principle is that whether the alternative remedy is fit to the gravity of offence. The penalty is awarded by the court by interpreting the circumstances of individual cases.The day were there when the Supreme Court in 1980s had been criticized on the ground that “The Court cannot give birth to a human being and hence how it can take away the life”. The Social activists like Human Rights Activists and AGOs are against the death penalty given by court. But as the heinous crimes are in increasing rate the courts are being serious about the serious types of offences. Because the death penalty is not a principal mode of punishment rather it is a major deterrent of effect to the future judiciary system and checks the preparing accused. The Supreme Court in Machhi Singh v. State of Punjab, (1983) 3 SCC 470 AIR 1983 SC 957 1983 SCC (Cri) 681 (1983) 3 SCR 413 held that the reasons why the community as a whole does not endorse the humanistic approach reflected in “death sentence in no case” doctrines are not for to seek.